Description of kinesthetic and kinetic motor praxis in older preschool children with logopathology - Olena Bielova; Svіtlana Konopliasta (IP Iermakov S.S., 2023)
Background and Study Aim. The development of kinesthetic and kinetic hand praxis in older preschool children is a prerequisite for successful learning in school conditions. The purpose of this study is to identify the current state of neuromotor functionality  kinesthetic and kinetic hand praxis, which affects readiness for schooling, in older preschool children with speech pathology. Material and Methods. Research methods are aimed at studying the components of neuromotor functionality: kinaesthetic and kinetic wrist praxis. To study the kinesthetic praxis of the hands, the task "Fine motility of the fingers" was used. Kinetic praxis was studied during the task "Differentiated movements of the hand". They studied the formation of object-kinetic praxis during "Performing actions with objects". Results. The results of the experimental study give a clear idea that there are significant differences in the formation of neuromotor functionality between the groups of children with logopathology and those with normotypical psychophysical development. In older preschool children with speech disorders, low abilities were found when performing tasks of kinaesthetic and kinetic praxis: wrist (fussy movements of fingers and hands; searching for the right position, the incorrect joining of fingers, hand positions; the presence of perseveration of previous movements; underdeveloped fine motility of fingers of hands; difficulties in subject activities). Children are passive during classes, they need constant support from the teacher. Conclusions. The revealed unformed state of neuromotor functionality confirms our hypothesis. Impairment of neuromotor function of kinesthetic and kinetic hand praxis is present in a significant percentage of preschoolers with speech disorders, which becomes a characteristic feature of this category of children and affects further physical, intellectual, and semiotic development.